Transformation of metal-organic frameworks for molecular sieving membranes - Wanbin Li (Nature Portfolio, 2016)
Metal-organic frameworks (MOFs) are attracting increasing attention as membrane components for molecular sieving due to the range of desirable properties they exhibit. Here, the authors employ in situ cation substitution to transform MOF topologies, and endow the membranes with improved separation capabilities.